2021
DOI: 10.32535/ijabim.v6i1.1085
|View full text |Cite
|
Sign up to set email alerts
|

A Construction of Entrepreneurial Personality Tests: Testing Archetype Personality Inventory in Entrepreneurship

Abstract: VUCA is about a hyper-competitive and unpredictable environment. It stands for volatility, uncertainty, complexity, and ambiguity. Personal attributes are necessary to navigate the VUCA environment. Studies in entrepreneurship show that narratives help people to connect different experiences. Literature shows that a narrative journey can be described through archetypes and relate to entrepreneurial behavior. This study aims to construct and validate measurements of entrepreneurial personality by adapting Pears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, unfortunately, attention to hard skills is still flat. Research showed (Waller et al, 2019) Global higher education in a VUCA world: Concerns and projections 26 (Ningthoujam, 2019) The VUCA Learner: Future-proof Your Relevance 27 (Shkarupeta et al, 2021) Strategies for Developing Competencies for the VUCA World 28 (Daud & Hanafi, 2022) A Seat at the (Ehlers, 2020) Digital Leadership in Higher Education 51 (Handayani et al, 2020) Exploring Skills Needed for Disruptive Digital Business 52 (Kennedy, 2020) Tantangan Pendidikan Tinggi Menghadapi Perkembangan Teknologi Digital dalam Era VUCA 53 (Poernomo, 2020) Peran Perguruan Tinggi Dalam Menyiapkan Pemimpin Masa Depan menghadapi Era VUCA 54 (Wikantiyoso et al, 2021) A Construction of Entrepreneurial Personality Tests: Testing Archetype Personality Inventory in Entrepreneurship 55 (Nair & Fahimirad, 2019) A qualitative research study on the importance of life skills on undergraduate students' personal and social competencies…”
Section: Hard Skills For Studentsmentioning
confidence: 99%
“…However, unfortunately, attention to hard skills is still flat. Research showed (Waller et al, 2019) Global higher education in a VUCA world: Concerns and projections 26 (Ningthoujam, 2019) The VUCA Learner: Future-proof Your Relevance 27 (Shkarupeta et al, 2021) Strategies for Developing Competencies for the VUCA World 28 (Daud & Hanafi, 2022) A Seat at the (Ehlers, 2020) Digital Leadership in Higher Education 51 (Handayani et al, 2020) Exploring Skills Needed for Disruptive Digital Business 52 (Kennedy, 2020) Tantangan Pendidikan Tinggi Menghadapi Perkembangan Teknologi Digital dalam Era VUCA 53 (Poernomo, 2020) Peran Perguruan Tinggi Dalam Menyiapkan Pemimpin Masa Depan menghadapi Era VUCA 54 (Wikantiyoso et al, 2021) A Construction of Entrepreneurial Personality Tests: Testing Archetype Personality Inventory in Entrepreneurship 55 (Nair & Fahimirad, 2019) A qualitative research study on the importance of life skills on undergraduate students' personal and social competencies…”
Section: Hard Skills For Studentsmentioning
confidence: 99%
“…Focusing on the field of entrepreneurship, scholars consider entrepreneurship as an economic act, but in the new era, entrepreneurship has taken on more significance and is an important manifestation of self-construction for entrepreneurs (Sun et al, 2022). Under the influence of different cultural orientations, there are differences in the self-construction process of entrepreneurs, which in turn affects the motivation of entrepreneurship (Wikantiyoso et al, 2021). The entrepreneur's motivation is not only to maintain survival and solve employment, but also to pursue self-worth and contribute to society (Kusa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Dimension of entrepreneurial personality with Pearson & Marr's archetype adaption force test in the environment of entrepreneurship shows that studies in entrepreneurship show that narratives help people connect colorful gests . The actuality of litterature shows that the narrative trip can be described through archetypes and is related to entrepreneurial geste (Wikantiyoso et al, 2021). Research on measuring the influence of the Big five inventory scale with entrepreneurial intentions shows that there is a compatibility of the big five inventory scale with entrepreneurial intentions (Erik, 2020).…”
Section: Introductionmentioning
confidence: 99%